Gastrointestinal endoscopy for intestinal dysplasia and neoplasia detection and management in Crohn’s disease: when and how? - Pessarelli, Tommaso; Piagnani, Alessandra; Tontini, Gian Eugenio; Bergna, Irene Maria Bambina; Amato, Arnaldo (Frontiers in Gastroenterology, 2025)
Patients with long-standing inflammatory bowel disease (IBD) involving the colon have an approximately 2–3-fold risk of colorectal cancer (CRC), which remains a leading cause of mortality in this population. However, data specifically assessing CRC incidence in Crohn’s disease (CD) are limited, and these patients also face an increased risk of small bowel cancer (SBC). Endoscopy plays a central role in CRC prevention, as well as in the detection and management of dysplasia and early CRC in CD. This review summarizes current evidence on the role of lower gastrointestinal endoscopy, as well as small bowel capsule endoscopy and device assisted enteroscopy, in this context. It provides practical guidance on the optimal use of these endoscopic techniques, considering patient- and disease-specific factors. Additionally, it highlights emerging endoscopic technologies and future perspectives in the field.